Improvement in simultaneous processing through metacognitive instruction - Ares Ferreirós, Martina; Alfonso Gil, Sonia; Rodríguez Enríquez, Mónica; Conde Rodríguez, Ángeles; Deaño Deaño, Manuel (Frontiers in Education, 2024)
This study presents the improvement generated in simultaneous processing by the application of metacognitive instruction to 3 rd grade primary education students. A pre-post-follow-up test design was used. The sample consisted of 30 students from one classroom. Two groups were formed; an intervention group comprising students in the classroom who presented difficulties in simultaneous processing, showing a cognitive weakness that compromises reading comprehension, and a comparison group comprising the rest of the students in the class. The instruments used were the Das-Naglieri Cognitive Assessment System (DN CAS), Assessment of Reading Comprehension (ACL) test and the Reading Awareness Scale (ESCOLA). The groups were equivalent in socioeconomic and cultural status and in successive processing. Reading and study variables were used as differentiators: simultaneous processing and reading awareness. A metacognitive training program based on the Planning Facilitation method was applied to the intervention group. The comparison group followed the usual curricular activities of the classroom and for the education level, according to the traditional teaching model. The program was implemented in 48 sessions over 12 weeks. After the intervention, the group with weakness improved significantly in simultaneous processing and reading awareness; the comparison group did not show any change in their initial scores. The metacognitive instruction that facilitates discussion between students and reflective verbalization about reading tasks promotes improvement in reading awareness and in the simultaneous processing necessary for reading comprehension.